The value of ammoniated hydrol in beef cattle wintering rations. - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Thirty Hereford heifer calves averaging about 400 pounds each were divided as ,equally as possible into three lots of 10 animals each. All lots received all the sorghum silage they would clean up each day. A mineral mixture of equal parts steamed bonemeal and salt and salt alone were fed free choice. Other ingredient's, which varied in the different rations were as follows: Lot 1-Control, 1 pound soybean oil meal + 3 pounds milo grain. Lot 2-Two pounds dehydrated ammoniated hydrol product + 2 pounds milo grain. Lot 3-0.6 pound soybean oil meal, 2 pounds liquid ammoniated hydrol, and 1. 9 pounds milo grain. All rations were calculated to contain approximately the same amount of protein equivalent and total digestible nutrients. The liquid ammoniated hydrol contained 14.4 percent protein equivalent and the dehydrated ammoniated hydrol product contained 21.2 percent protein equivalent. The dehydrated product is similar to Dex-Mo-Lass except that ammoniated hydrol was used instead of plain hydrol to dry on corn oil meal and corn gluten meal. Soybean oil meal was not used in Lot 2.
Keywords: Beef; Ammoniated hydrol; Protein; Heifers